2018
DOI: 10.26444/aaem/75802
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted iron metabolism in peritoneal fluid may induce oxidative stress in the peritoneal cavity of women with endometriosis

Abstract: Introduction and objective. Data on the possible role of peritoneal fluid free radical-mediated oxidative damage in the pathogenesis of endometriosis still remains inconsistent. The aim of the study was to determine iron metabolism markers and their influence on oxidative stress parameters in the peritoneal fluid of women with endometriosis. Materials and method. 110 women with endometriosis and 119 patients with benign ovarian cysts were included in the study. All visible peritoneal fluid was aspirated during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 25 publications
(37 reference statements)
3
24
0
Order By: Relevance
“…In this way, Alizadeh et al [26] showed that serum iron levels in patients with EMS were significantly increased and suggested that this metal ions could be a potent promoter of OS in EMS. The accumulation of iron ions was also reported by Polak et al [30] while studying the overall oxidative status of peritoneal fluid of EMS patients suggesting that iron metabolism could be disrupted in this disease. Furthermore, since iron could catalyze many ROS species production and was also implicated in cellular dysfunction, necrosis, and apoptosis, Chen, Hayashi, and co-authors [31,32] investigated the mitochondrial structure and function of endometrial stromal cells (ESCs) in ovarian endometriosis (OE) in relation to mitochondrial and iron metabolism.…”
Section: Oxidative Stress and Ems Oxidative Stress And Emssupporting
confidence: 70%
“…In this way, Alizadeh et al [26] showed that serum iron levels in patients with EMS were significantly increased and suggested that this metal ions could be a potent promoter of OS in EMS. The accumulation of iron ions was also reported by Polak et al [30] while studying the overall oxidative status of peritoneal fluid of EMS patients suggesting that iron metabolism could be disrupted in this disease. Furthermore, since iron could catalyze many ROS species production and was also implicated in cellular dysfunction, necrosis, and apoptosis, Chen, Hayashi, and co-authors [31,32] investigated the mitochondrial structure and function of endometrial stromal cells (ESCs) in ovarian endometriosis (OE) in relation to mitochondrial and iron metabolism.…”
Section: Oxidative Stress and Ems Oxidative Stress And Emssupporting
confidence: 70%
“…Women with endometriosis have increased oxidative stress in the peritoneal cavity. Data indicate that oxidative stress occurs mainly in the peritoneal cavity in women with advanced stage of the disease [ 154 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…Polak et al showed that the peritoneal fluid of women with endometriosis is characterized by impaired iron metabolism [ 154 ]. This is most likely related to the increased number of erythrocytes in the peritoneal cavity of women with endometriosis, which leads to a higher haemoglobin concentration in this environment.…”
Section: Biomarkersmentioning
confidence: 99%
“…Haem is involved in the initiation of lipid peroxidation, in which unsaturated fatty acids or other lipids are oxidated by free radicals to their respective peroxides [ 34 ]. Disturbances of the pro-/antioxidant balance that lead to oxidative stress are a recognized mechanism responsible for the development of endometriosis [ 35 ]. A diet rich in red meat can also be responsible for higher estradiol levels by which it leads to endometriosis.…”
Section: Resultsmentioning
confidence: 99%